2014
DOI: 10.1111/mcn.12136
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and determinants of malnutrition among pregnant women in eastern Ethiopia: evidence from rural, community‐based setting

Abstract: Maternal malnutrition is a worldwide public health problem affecting a high proportion of pregnant women. This study aimed to determine the magnitude and determinants of malnutrition among pregnant women in eastern Ethiopia. A cross-sectional study was conducted on 1731 pregnant women selected by a cluster random sampling method. Data on maternal anthropometry and other factors were gathered by trained data collectors. Mid-upper arm circumference < 22 cm defined malnutrition. Mixed-effect, multilevel logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
60
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 29 publications
21
60
10
1
Order By: Relevance
“…This is consistent with the result of survey done in Iran in which participants with scores ≥ six had greater body mass index, waist circumference, and waist-to hip ratio than in individuals with scores less than six [33]. The study is also similar to the community based study done in eastern Ethiopia in which pregnant women who improved their eating habits had a 53% lower risk of undernutrition than who did not [21]. The study done in Kenya also showed that pregnant women with better DDS had greater macro-and micronutrient intake when compared to pregnant women with low DDS [27].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with the result of survey done in Iran in which participants with scores ≥ six had greater body mass index, waist circumference, and waist-to hip ratio than in individuals with scores less than six [33]. The study is also similar to the community based study done in eastern Ethiopia in which pregnant women who improved their eating habits had a 53% lower risk of undernutrition than who did not [21]. The study done in Kenya also showed that pregnant women with better DDS had greater macro-and micronutrient intake when compared to pregnant women with low DDS [27].…”
Section: Discussionsupporting
confidence: 90%
“…The big discrepancy observed may be due to different MUAC cut-off points used to determine undernutrition. However, the finding from this study was higher than other findings from highlands of Ethiopia 19.06% from eastern Ethiopia [21].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Seasonal variation and the fact that this study was conducted during the known hunger season in the area might have contributed to the high rates of malnutrition among the PLW. Past studies from development settings in Ethiopia have reported a prevalence of 19.1% with a more lenient criterion of MUAC < 22 cm [22], clearly indicating that malnutrition rates could be higher during emergencies even after a period of interventions. In this study, there seems to be some connection between receiving ANC and acute malnutrition among PLW.…”
Section: Discussionmentioning
confidence: 91%
“…In developing nations including Ethiopia, burden of maternal and child undernutrition is very high. The prevalence of maternal undernutrition in Africa including Ethiopia found between 11%-36% (20)(21)(22)(23)(24)(25)(26)(27). The most acceptable explanation for this wide variation is likely to be the fact that contextual factors are major determinants of maternal undernutrition.…”
Section: Introductionmentioning
confidence: 99%